Surgical technique-microsurgery: Indications and techniques of microsurgery in general surgery and specialties - Irigaray, Alberto; Fossati Introzzi, Enrique; Fossati, Guillermo; Benedek, Pedro; Motta, Heber; Castillo, Luis; Blasiak, José (Cirugía del Uruguay, 1982)
In order to show to General Surgeons the indications and applications of the Microsurgery technic, a multidisciplinary panel, composed by Plastic Surgeons, Neurosurgeons, Traumatologists and ENT Surgeons, which in their respectives specialities practice microsurgery, are joined. The use of the microscope in several surgical branches, has allowed the development of an unsuspected number of posibilities, with excellent results.